Hubungan Usia Ibu Hamil Risiko Tinggi Dengan Kejadian Preeklampsia Berat (PEB) di RS. Dr. Oen Surakarta Periode 2013 - 2015 - Primadhani, Selly Anniszavuri; , Dr. Supanji Raharja, Sp.Og (K) (2017)
Background: Preeclampsia is a pregnancy-specific syndrome in the form of reduced organ perfusion due to vasospasm and endothelial activation, which is characterized by increased blood pressure and proteinuria. Preeclampsia occurs in pregnancy over 20 weeks, most visible at 37 weeks gestation. One of the factors causing preeclampsia is high risk maternal age. Objective: The aim of this study was to determine the relationship relationship between high risk maternal age and incidence of severe preeclampsia in Dr. Oen Hospital Surakarta. Methods: The study was observational analytic with cross sectional approach, sampling with purposive sampling, total sample of this study are 52 patients, 26 patients with severe preeclampsia and 26 without severe preeclampsia. Using secondary data obtained from medical in Dr. OEN Hospital Surakarta. The results were tested by chi-square test with SPSS 20.0 program Results: The amount of pregnant women who have a low risk age are 163 (80.7%) patients of 202 samples. Pregnant women who have a high risk age are 39 (19.3%) of 202 patients. After the Chi-Square test analysis found value significancy (p) is 0.000, which means there is a significant relationship between high risk maternal age and incidence of severe preeclampsia and prevalence ratio (PR) 4.59. Conclusion: There is a significant relationship between high risk maternal age and incidence of severe preeclampsia in Dr. Oen Hospital Surakarta period 2013-2015